2017
DOI: 10.1534/genetics.116.194449
|View full text |Cite
|
Sign up to set email alerts
|

Moving Beyond Managing Realized Genomic Relationship in Long-Term Genomic Selection

Abstract: Long-term genomic selection (GS) requires strategies that balance genetic gain with population diversity, to sustain progress for traits under selection, and to keep diversity for future breeding. In a simulation model for a recurrent selection scheme, we provide the first head-to-head comparison of two such existing strategies: genomic optimal contributions selection (GOCS), which limits realized genomic relationship among selection candidates, and weighted genomic selection (WGS), which upscales rare allele … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
81
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(83 citation statements)
references
References 35 publications
2
81
0
Order By: Relevance
“…That is, the result is driven by the fact that mislabeling reduces the negative impact that GS has on genetic variance. Thus, it seems likely that under optimal use of GS, in which genomic data can be used to maximize selection gain while minimizing inbreeding or loss of genetic diversity (Goddard, 2009;Jannink, 2010;Yabe et al, 2016;De Beukelaer et al, 2017;Lin et al, 2017), the impact of mislabeling would be greater than observed here. When using such methods, the mislabeling might not only reduce gain but also disrupt efforts at genetic diversity maintenance (e.g., affect estimates of favorable allele frequencies used to weight rare favorable alleles, or estimates of the relationships among selected individuals used to minimize those relationships).…”
Section: Suggestion For Breedingmentioning
confidence: 80%
“…That is, the result is driven by the fact that mislabeling reduces the negative impact that GS has on genetic variance. Thus, it seems likely that under optimal use of GS, in which genomic data can be used to maximize selection gain while minimizing inbreeding or loss of genetic diversity (Goddard, 2009;Jannink, 2010;Yabe et al, 2016;De Beukelaer et al, 2017;Lin et al, 2017), the impact of mislabeling would be greater than observed here. When using such methods, the mislabeling might not only reduce gain but also disrupt efforts at genetic diversity maintenance (e.g., affect estimates of favorable allele frequencies used to weight rare favorable alleles, or estimates of the relationships among selected individuals used to minimize those relationships).…”
Section: Suggestion For Breedingmentioning
confidence: 80%
“…With proper constraints, optimal contribution can either drive means for short-term gains while exhausting genetic variability, or achieve modest gains while maintaining genetic variation for long-term sustainability. Use of optimal contributions is widespread in animal breeding applications, and has recently been adopted for a few plant breeding applications (Lin et al 2017; De Beukelaer et al 2017; Cowling et al 2017). Gorjanc et al (2018) show that incorporating optimal contributions with mate selection can further increase genetic gain for the two-part rapid-cycle plant breeding program of Gaynor et al (2017).…”
Section: Introductionmentioning
confidence: 99%
“…(1 − ) ( ) + ( ), where is the weight balancing the expected gain ( ) and constraint 507 ( ) (De Beukelaer et al 2017). However, the appropriate choice of is difficult and is not explicit 508 either in terms of expected diversity nor expected gain.…”
Section: Ucpc Based Optimal Cross Selection 476mentioning
confidence: 99%
“…pairing of candidates, differential evolutionary algorithms have been suggested (Storn 73 and Price 1997;Kinghorn et al 2009;Kinghorn 2011). Using the concept of optimal contribution 74 selection for mating decisions is common in animal breeding (Woolliams et al 2015) and is increasingly 75 adopted in plant breeding (Akdemir and SĂĄnchez 2016;De Beukelaer et al 2017;Lin et al 2017;76 Gorjanc et al 2018;Akdemir et al 2018). 77…”
Section: Introductionmentioning
confidence: 99%